Machado de Assis na imprensa do século XIX: práticas, leituras e leitores - Farias, Vírna Lúcia Cunha de (2013)
The newspaper was configured in the 19th century as the main support for circulation of writings and dissemination of literature. In Brazil, in accordance with European models, especially French ones, this support became the main gateway for those who wished to enter in the world of letters. Machado de Assis, for example, entered into journalism with 15 years old and published most of his works first in the pages of newspapers and periodicals which circulated in Rio de Janeiro from 1854 to 1908. Noticing the importance of the press to the author s career, we investigate to what extent the editorial profile of each newspaper in which Machado collaborated influenced in his imagination and writing. We seek to show to what extent these supports may clarify aspects of Machado s work, such as aesthetic differences among some of his novels. We state that such differences are related to the necessity which the author had to adjust his pen to the public presupposed in each newspaper editorial. Most of the critics about the author attribute the aesthetic variations of his work to a supposed crisis he faced when he completed 40 years old. It is noticed that in stating such reading hypothesis, it takes into account only the publications in books of Machado s production. To reach the aim we proposed, it was necessary, at first, to reflect about the relation press/literature in the 19th century to see questions such as the submission of the authors to standards of writing required by the market. Then we suggest a division of Machado s production, considering his collaboration for periodicals and genres he produced more in each moment. Next, we trace the editorial profile of A Estação, woman s magazine in which Machado de Assis published a large part of his short stories and the novel QuincasBorba. The survey of sections of this periodical became the core of our research, because it helped us in proving the premise of the author s adequacy to the supports in which each work would circulate, since we ensure that it was for the reader of this periodical that the novelist wrote the first version of QuincasBorba. In the fourth chapter, we observe to what extent the fashion presented in A Estaçãoinfluenced the author s imagination in the creation of characters and description of habits. Finally, we make a parallel reading of the fashion magazine, in the publication of QuincasBorbapresented in the magazine and the first edition of the novel in book, published two months after the end of circulation of the narrative in series. We start from the premise that Machado de Assis, at the time of writing, thought simultaneously in two narratives: one that would fit the diversity the magazine s readers, and another that would be published as a book later.